Functional and morphological analysis of the subretinal injection of retinal pigment epithelium cells - Engelhardt, Maren (Visual neuroscience, 2012)
Replacement of retinal pigment epithelium (RPE) cells by transplantation is a potential treatment for some retinal degenerations. Here, we used a combination of invasive and noninvasive methods to characterize the structural and functional consequences of subretinal injection of RPE cells. Pigmented cells from primary cultures were injected into albino mice. Recovery was monitored over 8 weeks by fundus imaging, spectral domain optical coherence tomography (sdOCT), histology, and electroretinography (ERG). sdOCT showed that retinal reattachment was nearly complete by 1 week. ERG response amplitudes were reduced after injection, with cone-mediated function then recovering better than rod function. Photoreceptor cell loss was evident by sdOCT and histology, near the site of injection, and is likely to have been the main cause of incomplete recovery. With microscopy, injected cells were identified by the presence of apical melanosomes. They either established contact with Bruch’s membrane, and thus became part of the RPE monolayer, or were located on the apical surface of the host’s cells, resulting in apposition of the basal surface of the injected cell with the apical surface of the host cell and the formation of a series of desmosomal junctions. RPE cell density was not increased, indicating that the incorporation of an injected cell into the RPE monolayer was concomitant with the loss of a host cell. The transplanted and remaining host cells contained large vacuoles of ingested debris as well as lipofuscin-like granules, suggesting that they had scavenged the excess injected and host cells, and were stressed by the high digestive load. Therefore, although significant functional and structural recovery was observed, the consequences of this digestive stress may be a concern for longer-term health, especially where RPE cell transplantation is used to treat diseases that include lipofuscin accumulation as part of their pathology.
Gesehen am 06.11.2018